Effectiveness of Positive Psychology Concepts Training on Parental Self-Efficacy, Psychological Empowerment, and Assertiveness in Mothers of Children with Learning Disabilities - Mirzaei, Parvin (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to evaluate the effectiveness of positive psychology concepts training on parenting self-efficacy, psychological empowerment, and assertiveness in mothers of children with learning disabilities.Methods and Materials: The research employed a quasi-experimental pretest-posttest design with a control group. The statistical population consisted of mothers with children diagnosed with learning disabilities who attended educational and rehabilitation centers in Gilan-e Gharb during the first quarter of 2025. A total of 20 participants were selected through purposive sampling and randomly assigned to experimental (n = 10) and control (n = 10) groups. The experimental group received an eight-session, 90-minute intervention based on Seligman’s positive psychotherapy model, while the control group received no intervention. Measurement tools included the Parenting Self-Efficacy Questionnaire (Dumka et al., 1996), the Psychological Empowerment Questionnaire (Spreitzer, 1999), and the Rathus Assertiveness Schedule (1973). Data were analyzed using univariate and multivariate ANCOVA with SPSS-22.Findings: ANCOVA results showed a significant difference between the experimental and control groups in posttest scores for parenting self-efficacy (F = 3.134, p = .017), indicating the intervention’s positive effect. Psychological empowerment also significantly improved across all subscales in the experimental group, with large effect sizes observed for sense of meaning (η² = .635), competence (η² = .714), autonomy (η² = .691), impact (η² = .596), and participation (η² = .763). Assertiveness scores in the experimental group improved significantly as well, although the effect size was moderate (F = 3.013, p = .068). These results confirm the effectiveness of the intervention in enhancing the targeted psychological variables.Conclusion: Training based on positive psychology concepts significantly improved parenting self-efficacy, psychological empowerment, and assertiveness among mothers of children with learning disabilities, suggesting that strength-based interventions offer effective support for maternal well-being and parenting performance.